1994
DOI: 10.1044/jshr.3704.789
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Airway Resistance of Older Men and Women as a Function of Vocal Sound Pressure Level

Abstract: This study examined laryngeal airway resistance (RLAW) in 10 healthy male and 10 female subjects within three age groups (55:0–64:11; 65:0–74:11; and 75:0+ years). A noninvasive procedure (Smitheran & Hixon, 1981) was employed to investigate RLAW at four vocal sound pressure levels (SPL) (25th, 50th, 75th percentiles of the SPL range, and comfortable voice level [CV]). RLAW values for the oldest group of females were found to be higher at each SPL percentile than those of the two younger age groups. The ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
15
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
9
15
1
Order By: Relevance
“…This is consistent with the findings of previous studies. 21,[23][24] This finding is also in agreement with the results obtained by Higgins and Saxman 22 for their female subjects. In contrast to their findings for females, Higgins and Saxman 22 found that elderly males older than 69 years exhibited significantly greater estimated subglottal pressures as compared with younger males between 20 and 31 years of age.…”
Section: Age Effectssupporting
confidence: 95%
See 2 more Smart Citations
“…This is consistent with the findings of previous studies. 21,[23][24] This finding is also in agreement with the results obtained by Higgins and Saxman 22 for their female subjects. In contrast to their findings for females, Higgins and Saxman 22 found that elderly males older than 69 years exhibited significantly greater estimated subglottal pressures as compared with younger males between 20 and 31 years of age.…”
Section: Age Effectssupporting
confidence: 95%
“…13 However, it is consistent with a large number of studies, which have reported that males demonstrate significantly greater airflow rates in comparison to females. 1,[22][23][24][25][26][31][32][33] CONCLUSIONS Because age-and gender-related changes were found for some measures, one must account for these two variables when assessing phonatory aerodynamics using the PAS. Even though the results of the present study are consistent with previous findings reported in the literature, there remains a clear need to further develop adult normative data using the PAS.…”
Section: Gender Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to be able to distinguish changes that are associated with normal aging process from those that are associated with pathological processes co-occurring with aging. 24 …”
Section: Introductionmentioning
confidence: 97%
“…As with the respiratory changes, the changes in the larynx begin earlier and occur to a greater extent in men than in women (Hirano et al, 1983;Kahane, 1987;Ximenes Filho et al, 2003). Age-related anatomical changes in the larynx are likely to result in reduced glottal closure during vocal fold vibration (Biever & Bless, 1989;Honjo & Isshiki, 1980) and reduced laryngeal airway resistance (Holmes, Leeper, & Nicholson, 1994;Melcon, Hoit, & Hixon, 1989). However it is not clear if this change in laryngeal airway resistance results in increased air wastage during vocal fold vibration (Sapienza & Dutka, 1996).…”
Section: Introductionmentioning
confidence: 99%